Electrochemical Detection of Serum Antibodies Against Mycobacterium avium Subspecies paratuberculosis - Hatate, Kaoru; Rice, J. Hunter; Parker, Karsten; Wu, J. Jayne; Turner, Amy; Stabel, Judith R.; Eda, Shigetoshi (Frontiers in Veterinary Science, 2021)
Mycobacterium avium subsp. paratuberculosis causes a chronic inflammatory intestinal disease, called Johne’s disease in many ruminants. In the dairy industry, Johne’s disease is responsible for significant economic losses due to decreased milk production and premature culling of infected animals. Test-&-cull strategy in conjunction with risk management is currently recommended for Johne’s disease control in dairy herds. However, current diagnostic tests are labor intensive, time consuming and/or too difficult to operate on site. In this study, we developed a new method for detection of anti-M. paratuberculosis antibodies from sera of Johne’s disease -affected animals. M. paratuberculosis antigen-coated magnetic beads were sequentially reacted with bovine serum followed by horseradish peroxidase-labeled secondary antibody. Reaction of horseradish peroxidase with its substrate was then quantitatively measured electrochemically using a specific redox-active probe, ferrocyanide. After optimization of electrochemical conditions and concentration of the redox-active probe, we showed that the new electrochemical detection method could distinguish samples of Johne’s disease -affected cattle from those of Johne’s disease -negative cattle with greater separation between the two groups of samples (higher signal-to-noise) when compared with a conventional colorimetric testing method. Since electrochemical detection can be conducted with an inexpensive, battery-operated portable device, this new method may form a basis for development of an on-site diagnostic system for Johne’s disease.